Optimisation of nursery rearing for megalopa of giant mud crab Scylla serrata (Forskal, 1775) - Antony, Jose; Balasubramanian, C. P.; Balamurugan, J.; Sandeep, K. P.; Biju, I. F.; Vijayan, K. K. (Indian Journal of Fisheries, 2019)
Three nursery rearing trials were conducted to overcome the inconsistent survival of megalopa of the giant mud crab Scylla serrata (Forskal, 1775) during metamorphosis to crab instar. In the first trial, 3-4 days old megalopa (4.73 mg mean body weight) were stocked in hapas erected in outdoor brackishwater ponds and indoor fiberglass (FRP) tanks at densities of 500 nos. m-2 and 1 no. l-1 respectively and reared for 15 days using minced clam meat (Meretrix casta) as feed. Outdoor hapas were provided with seaweed, Gracilaria tenuistipitata as shelter. Mean survival rate of crab instar following three consecutive runs were significantly higher (p